IMPORTÂNCIA DO REÚSO DE ÁGUA NO CENTRO DE TREINAMENTO DE COMBATE A INCÊNDIO: ESTUDO DE CASO SAMPLING PLANEJAMENTO - Correia Neto, Severino Joaquim (2009)
The consumption of freshwater in the world has grown dramatically, due to the increase of population in urban areas, irrigation of agri-business and the use of water in industrial processes, leading consequently municipal sewage and industrial. This evokes the need for major duty of saving, reduce, recycle and reuse to develop processes that do not come in the opposite direction of society, or are based on the precautionary principle, considering the possibility of contamination of a chemical and microbiological present the effluents. This study evaluated a critical processes for reuse in general and more specifically in Training Centers Fire Fighting training which consumes considered volume of water as the extinguishing agent. The technologies developed simple and creative prove the success of water reuse in the fight against waste.